Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00262-007-0410-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory pretreatment enables an efficient dendritic cell-based immunotherapy against established tumors

Abstract: Although animals can be immunized against the growth of some tumor implants, most of the attempts to use immunotherapy to cause the regression of animal and human tumors once they have become established have been disappointing even when strongly immunogenic tumors were used as target. In this paper, we demonstrate that the failure to achieve an efficient immunological treatment against an established strongly immunogenic murine fibrosarcoma was paralleled with the emergence of a state of immunological unrespo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 54 publications
2
38
1
Order By: Relevance
“…However, it was recently suggested that oxidized amino acids, such as m-and o-Tyr, may also be generated from free amino acids that subsequently could be incorporated into proteins during synthesis (48,49). We previously observed that the serum antitumor activity attributed to m-and o-Tyr was strongly inhibited by agents that reduced the number of myeloid-derived suppressor cells (MDSC) and oxidative damage, and that in tumor-bearing mice (including the LB tumor model used in this work) and some cancer patients, MDSCs that produced large amounts of reactive oxygen species accumulated progressively in circulation (46,(50)(51)(52)(53). On the basis of these results, we suggested that free m-and o-Tyr present in the serum from tumor-bearing mice will be produced, at least in part, when circulating molecules of Phe are oxidized by hydroxyl radicals released by MDSC.…”
Section: Origin Of Tyr Isomers and Putative Mechanisms Of Tumor Inhibmentioning
confidence: 99%
“…However, it was recently suggested that oxidized amino acids, such as m-and o-Tyr, may also be generated from free amino acids that subsequently could be incorporated into proteins during synthesis (48,49). We previously observed that the serum antitumor activity attributed to m-and o-Tyr was strongly inhibited by agents that reduced the number of myeloid-derived suppressor cells (MDSC) and oxidative damage, and that in tumor-bearing mice (including the LB tumor model used in this work) and some cancer patients, MDSCs that produced large amounts of reactive oxygen species accumulated progressively in circulation (46,(50)(51)(52)(53). On the basis of these results, we suggested that free m-and o-Tyr present in the serum from tumor-bearing mice will be produced, at least in part, when circulating molecules of Phe are oxidized by hydroxyl radicals released by MDSC.…”
Section: Origin Of Tyr Isomers and Putative Mechanisms Of Tumor Inhibmentioning
confidence: 99%
“…The following tumors were also used: MC-C (fibrosarcoma), CEI (epidermoid carcinoma), and the highly metastatic C7HI (mammary adenocarcinoma), that were described previously (9,22,23).…”
Section: Tumorsmentioning
confidence: 99%
“…Western blotting was carried out with standard techniques as described (23) and analyzed by ImageQuant software. The following antibodies were used: anti-p-Erk 1/2, anti-ERK 1/2, anti-p-STAT3, anti-STAT3 (Santa Cruz), and anti-b-actin (Cell Signaling Technology).…”
Section: Western Blottingmentioning
confidence: 99%
“…Methylcolanthrene-induced murine fibrosarcoma (MCC) is a highly immunogenic tumor that elicits an early specific antitumor immune reaction, which is not strong enough to impede tumor growth (18)(19)(20)(21). The antitumor response declines at a certain tumor volume (~500 mm 3 ) and disappears comprising a state of tolerance (18)(19)(20)(21). Immunological characteristics of MCC and its rapid growth in vivo make it a suitable model to study mechanisms underlying tumor immunity and tumor-induced immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence that accounts for the role of B cells in tumor-induced immunosuppression includes the existence of human B cells with a regulatory phenotype in solid tumors (11), the B cell-mediated induction of Tregs expansion (12)(13)(14) and the increase of tumor growth (12,(15)(16)(17). Methylcolanthrene-induced murine fibrosarcoma (MCC) is a highly immunogenic tumor that elicits an early specific antitumor immune reaction, which is not strong enough to impede tumor growth (18)(19)(20)(21). The antitumor response declines at a certain tumor volume (~500 mm 3 ) and disappears comprising a state of tolerance (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%